Centre-Periphery and the Global Early Modern: Some Historiographical Reflections - Plakotos, Giorgos (Historein, 2021)
The essay draws on the notion of centre-periphery, first, to discuss the politics of history writing and international research and, second, to address some interpretive assumptions that have informed the study of early modernity from a global perspective in the fields of early modern history and studies over the last two decades. The essay argues that appeals to a “global” early modern past often obscure asymmetries of power both as far as the past itself is concerned and the politics of history writing. The use of periodisation concepts such as the “early modern” and the “Renaissance”, which have been developed in European history and historiography, and the distrust of postcolonial theory undermine globality as an interpretive perspective and the endeavour to shake the burden of Eurocentrism.